Technology-Based Learning Innovation in Geometry Transformation Using the Desmos Application to Enhance Students' Visualization and Academic Achievement - Rahmatika, Ahmad; Mahriyuni, Mahriyuni (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2025)
This study focuses on the development and implementation of an innovative learning model for geometric transformations by integrating technology through the use of the Desmos application as an interactive instructional tool. Geometric transformation is a fundamental concept in mathematics but is often regarded as abstract and challenging for students to grasp. This research aims to improve students’ conceptual understanding and motivation by providing a dynamic and visual learning environment using Desmos, a user-friendly digital graphing platform. The study employs a development research methodology consisting of stages such as design, implementation, and evaluation of the learning media. Data collected through observations and student feedback demonstrate that incorporating Desmos in the learning process significantly enhances student engagement, simplifies the visualization of complex geometric concepts, and creates a more enjoyable and effective learning experience. The findings suggest that technology-based innovations like this can serve as effective alternatives to traditional teaching methods in mathematics education, particularly for teaching geometric transformation material.